Lespedeza bicolor Extract Improves Amyloid Beta25 – 35-Induced Memory Impairments by Upregulating BDNF and Activating Akt, ERK, and CREB Signaling in Mice - Ko, Yong-Hyun; Shim, Kyu-Yeon; Kim, Seon-Kyung; Seo, Jee-Yeon; Lee, Bo-Ram; Hur, Kwang-Hyun; Kim, Young-Jung; Kim, Seong-Eon; Do, Moon Ho; Parveen, Amna; Kim, Sun Yeou; Lee, Seok-Yong; Jang, Choon-Gon (Planta Medica, 2019)
Lespedeza bicolor, a traditional herbal medicine widely used in Australia, North America, and Eastern Asia, has various therapeutic effects on inflammation, nephritis, hyperpigmentation, and diuresis. In this study, to evaluate the effects of L. bicolor on cognitive function, we examined whether L. bicolor improved amyloid beta-induced memory impairment and assessed the possible mechanisms in mice. Catechin, rutin, daidzein, luteolin, naringenin, and genistein were identified in the powdered extract of L. bicolor by HPCL-DAD analyses. In behavioral experiments, L. bicolor (25 and 50 mg/kg, p. o.) significantly improved amyloid beta25 – 35 (6 nmol, intracerebroventricular)-induced cognitive dysfunction in the Y-maze, novel recognition, and passive avoidance tests. Our molecular studies showed L. bicolor (25 and 50 mg/kg, p. o.) significantly recovered the reduced glutathione content as well as increased thiobarbituric acid reactive substance and acetylcholinesterase activities in the hippocampus. Furthermore, we found that L. bicolor significantly increased the expression of brain-derived neurotrophic factor, and phospho-Akt, extracellular signal-regulated kinase, and cAMP response element binding caused by amyloid beta25 – 35 in the hippocampus. In conclusion, L. bicolor exerts a potent memory-enhancing effect on cognitive dysfunction induced by amyloid beta25 – 35 in mice.
Keywords: Lespedeza bicolor; Leguminosae; amyloid beta; learning and memory; brain-derived neurotrophic factor; Alzheimerʼs disease